Distribution and antifungal susceptibility of Candida species isolated from clinical samples in southern Brazil - Tatiani Karini Rensi Botelho; Letícia Jacobi Danielli; Milena Seide; Pâmela Pacassa Borges; Alexandre Bella Cruz (Universidade de São Paulo, 2022)
Abstract Invasive infections caused by Candida species have been strongly associated with poor prognosis and high resistance rates to some antifungals. This study aimed to identify Candida species isolated from different anatomical sites and to describe their susceptibility profile to antifungals. Ninety-four clinical isolates of Candida were obtained from a Medical Laboratory of Santa Catarina/Brazil. Species identification was performed by MALDI-TOF MS. Susceptibility assays were performed as described by Clinical Laboratory Standard Institute (CLSI) microboth method. Among the analyzed samples, C. albicans was the pathogen most incident (59.9%) followed by C. parapsilosis complex (14.9%), C. glabrata complex (8.5%), and C. tropicalis (6.3%). 37 Candida strains were isolated from vaginal content (39.3%), 21 from the nail (22.4%), 8 from tracheal aspirates (8.5%), and 7 from urine (7.4%). Together, the Candida isolates presented decreased susceptibility to azole drugs, mainly to fluconazole and itraconazole. Amphotericin B showed sensibility in 95.7% of samples analyzed. Previous knowledge about etiology and antifungal susceptibility becomes indispensable to conduct an efficient treatment.